Credit Scoring, Response Modelling and Insurance Rating A Practical Guide to Forecasting Consumer Behaviour - Finlay, S. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2010)
Every year, financial services organizations make billions of dollars worth of decisions using automated systems. For example, who to give a credit card to and the premium someone should pay for their home insurance. This book explains how the forecasting models, that lie at the heart of these systems, are developed and deployed.